Plan de negocio para la creación de un complejo turístico en la provincia de Pastaza, parroquia el Triunfo, en el periodo 2014 - Juank Tiwi, Lenin Rolando (2016)
The present research work was made at "El Triunfo" parish in Pastaza Province, in order to create the "El Olimpo", tourist complex aimed to satisfy distraction needs of consumers or tourists, in correspondence the implementation of the fundamental axis that pursues will the new productive matrix. To establish the correct research is applied a market study which impulse the supply, demand, competition analysis and unsatisfied demand, in manner that will contribute to increase the sales volume at its first period of operation, through the using surveys and observation, the influx of foreign, national tourists shows groups of potential customers with preferences for making historical tourism, recreation, adventure….